ANALISIS SUMBER DAN PENGGUNAAN MODAL KERJA PADA MINI MARKET PELANGI JAMBI - Pupu Sopini; Chairani Yuli Trifani (Universitas Batanghari Jambi, 2017)
The working capital having nature of flexible, big or small working capital can be added or reduced in accordance with need company. Control working capital that will exactly ensure of continuity the operations firm efficien and economical. The objective of analyze sources and use working capital to how working capital used. Research objectives: 1) to know the sources and the use of capital work At Mini Market Pelangi Period 2012-2016. 2) to analyze the use of capital work At Mini Market Pelangi Period 2012-2016was accurate. The data be used based on secondary data Mini Market Pelangi Period 2012–2016. The method of analysis the data used descriptive quantitative by means analysis trend horizontal and analysis change working capital. The results of the study sources and use of working capital at Mini Market Pelangi Period 2012-2016, others 1) Period 2012-2013 increased by 25,08 percent indicated excess working capital 2013 of Rp. 106.897.235,-. 2) Period 2013-2014 increased by 96,06 percent indicated excess working capital 2014 of Rp. 306.741.930,-. 3) Period 2014-2015 decreased by 1.513,66 percent indicated indicated working capital 2014 of Rp. 190.648.412,-. 4) Period 2015-2016 increased by 124,65 percent indicated excess working capital 2016 of Rp. 253.348.728,-. The use of capital work at Mini Market Pelangi Period 2012-2016, others: 1) use of working capital the period 2012-2013 was accurate. 2) use of working capital the period 2013-2014 was accurate. 3) use of working capital the period 2014-2015 was inaccurate. 4) use of working capital the period 2015-2016 was accurate.Keyword : Source Working Capital, Use Working Capital.